2019
DOI: 10.2147/ijn.s214585
|View full text |Cite
|
Sign up to set email alerts
|

<p>Delivery luteolin with folacin-modified nanoparticle for glioma therapy</p>

Abstract: Background: Glioblastoma mutliforme is the most common and has the poorest prognosis of any malignant tumor of the central nervous system. Luteolin, the most abundant xanthone extracted from vegetables and medicinal plants, has been shown to have treatment effects in various cancer cell types. Luteolin is however, hydrophobic and has poor biocompatibility, which leads to low bioavailability. Patients and methods: In this study, folic acid modifiedpoly(ethylene glycol)-poly(ecaprolactone) (Fa-PEG-PCL) nano-mice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(67 citation statements)
references
References 40 publications
1
66
0
Order By: Relevance
“…A strategy for increase the bioavalibility of luteolin was to encapsulate the flavone in folic acid-modified poly(ethyleneglycol)-poly(caprolactone) (Fa-PEG-PCL) nano-micelles that make luteolin much more efficient with respect to when it is in its free form, reducing the concentration needed to kill cells, such as in glioblastoma. The same effect was also reported when xenograft mice were used [130].…”
Section: Luteolinsupporting
confidence: 76%
“…A strategy for increase the bioavalibility of luteolin was to encapsulate the flavone in folic acid-modified poly(ethyleneglycol)-poly(caprolactone) (Fa-PEG-PCL) nano-micelles that make luteolin much more efficient with respect to when it is in its free form, reducing the concentration needed to kill cells, such as in glioblastoma. The same effect was also reported when xenograft mice were used [130].…”
Section: Luteolinsupporting
confidence: 76%
“…Of the 24 articles identified in the Cochrane Library, no articles were included, as 16 articles were reviews, 5 were protocols, and 3 were clinical articles in the screening analysis. In total, only 27 full-text articles not duplicated were included in this systematic review [ 32 , 34 , 38 , 41 , 43 , 44 , 45 , 48 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], as illustrated in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…The major tumoral cell characteristics used in the selected studies in our review are shown in Table 1 . Of 27 selected studies for this review, 19 studies (70%) [ 32 , 34 , 38 , 43 , 45 , 48 , 52 , 53 , 55 , 56 , 57 , 58 , 59 , 62 , 63 , 64 , 65 , 66 , 67 ] used tumor cells from a human source, 6 (22%) [ 41 , 51 , 54 , 60 , 61 , 68 ] used tumor cell from rats, and 3 studies (11%) [ 44 , 50 , 66 ] used cells from mice. The study by Agemy [ 66 ] used human and mice tumor cell sources and also used lentivirus H-RasV12-shp53 to induce glioma cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations